Neuroprotective Effect of Brain-Derived Neurotrophic Factor (BDNF) on Cerebral Infarct Volume and Clinical Severity of Acute Ischemic Stroke - Satrio Wicaksono; Andi Kurnia Bintang; Muhammad Akbar; Muhammad Yunus Amran; Cahyono Kaelan; Isra Wahid (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2024)
ABSTRACT Background: Brain-Derived Neurotrophic Factor (BDNF) plays a crucial role in protecting nerves following ischemic stroke. The neuroprotective effects of BDNF on cerebral infarct volume and clinical severity after ischemic stroke need to be further studied in-depth. Purpose(s): The purpose of this study is to understanding the relationship between BDNF levels, cerebral infarct volume, and the severity of clinical conditions in acute ischemic stroke patients. Methods: This study is an observational nalytical research with a cross-sectional design. A total of 30 individuals who meet the inclusion criteria were included as samples. Cerebral infarct volume was measured using non-contrast head CT scans with the Broderick formulation, and clinical severity was assessed using the National Institutes of Health Stroke Scale (NIHSS). The collected data were then analyzed using statistical tests. Results: There is a significant relationship between serum BDNF levels and cerebral infarct volume with a p-value of 0.004 and a correlation coefficient (r) of -0.509. Similarly, a significant relationship exists between serum BDNF levels and NIHSS with a p-value of 0.042 and a correlation coefficient (r) of -0.374. Conclusion: There is a negative correlation between serum BDNF levels and cerebral infarct volume in acute ischemic stroke patients, as well as a negative correlation between serum BDNF levels and clinical severity in acute ischemic stroke patients. Keywords: BDNF; Infarct Cerebri Volume; NIHSS